2007
DOI: 10.1103/physrevlett.99.066805
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Plasmon-Polariton Assisted Diffraction in Periodic Subwavelength Holes of Metal Films with Reduced Interplane Coupling

Abstract: Metal films grown on Si wafer perforated with a periodic array of subwavelength holes have been fabricated and anomalous enhanced transmission in the mid-infrared regime has been observed.High order transmission peaks up to Si(2,2) are clearly revealed due to the large dielectric constant contrast of the dielectrics at the opposite interfaces. Si(1,1) peak splits at oblique incidence both in TE and TM polarization, which confirms that anomalous enhanced transmission is a surface plasmon polaritons (SPPs) assis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…The tunable optical properties of ring-shaped materials can also be achieved by varying the diameter and thickness of the ring [4] and by patterned structures of NRs and NHs [5]. On the other hand, filling the NHs with functional materials, quantum confined structures and their associated quantized effects may be demonstrated in a variety of host structures such as plastics and glasses [6][7][8].…”
Section: Introductionmentioning
confidence: 98%
“…The tunable optical properties of ring-shaped materials can also be achieved by varying the diameter and thickness of the ring [4] and by patterned structures of NRs and NHs [5]. On the other hand, filling the NHs with functional materials, quantum confined structures and their associated quantized effects may be demonstrated in a variety of host structures such as plastics and glasses [6][7][8].…”
Section: Introductionmentioning
confidence: 98%
“…It is generally considered that the mechanism of the enhanced transmission is due to the excitation of surface plasmon polaritons (SPPs) in a metallic film with periodical hole arrays [8][9][10]. However, K. J. Klein et al [11] demonstrated experimentally that extraordinary light transmission is strongly influenced by the hole shape.…”
Section: Introductionmentioning
confidence: 98%
“…Different physical models have been proposed to explain the unusual transmission enhancement, such as surface plasmon polariton (SPP) models [1][2][3], composite diffracted evanescent wave models [4,5], dynamical diffraction [6], waveguide mode [7], and cavity resonances [8]. Though the mechanism for the transmission enhancement is still under debate, researchers have found that the EOT in visible, near infrared, and terahertz range is sensitive to many physical and geometrical parameters including the film material [9][10][11], film thickness [12][13][14], geometry symmetry [15][16][17][18][19], lattice constant [16,[20][21][22][23], as well as hole size [20,[24][25][26][27] and hole shape [28][29][30][31][32]. This provides us with many degrees of freedom for the manipulation of light propagation.…”
Section: Introductionmentioning
confidence: 98%